Hubungan Stress Dan Fatique Dengan Kualitas Hidup Pada Pasien Gagal Jantung Di RS. Mitra Medika Medan - Pakpahan, Jun Edy Samosir; Jesmo Aldoran Purba; Nefonavratilova Ritonga (Universitas Aufa Royhan, 2025)
The prevalence of heart failure in the world increases every year, in heart failur patients psychological problems will arise such as stress, decreased sleep quality, and ongoing fatigue (fatigue) which will cause impaired ability to carry out daily activities. This can worsen clinical conditions and reduce quality of life. The aim of this study was to determine the relationship between stress, sleep quality and fatigue with quality of life in patients with heart failure. This research method is quantitative with a cross-sectional research design. The sample for this research was outpatients at Mitra Medika Hospital in Medan with a total sample of 52 people. Data were collected using the Minnesota Living with Heart Failure Questionnaire, Depression Anxiety and Stress Scale 21, Pittsburgh Sleep Quality Index, and FACIT Fatigue Scale. The research technique uses statistical test analysis, namely the Chi-Square Test with a significance of 0.05. The results showed that 38.8% of heart failure patients had moderate stress, and 53.8% had fatigue, and 73.1% had low quality of life and there was a significant relationship between stress (p=0.000), and fatigue (p=0.000) with quality of life. Emotional and social support is expected from family, community and health workers, such as information support, education on actions that patients can take, concern, and helping patients to find a comfortable environment.